Pengaruh Green Perceived Value (GPV) dan Green Brand Knowledge terhadap Purchase Intention to Buying Green Product Melalui Attitude Toward Purchasing Green Products - Prasetyo Hartanto; Ratih Hurriyati; Puspo Dewi Dirgantari (Jurnal Manajemen dan Organisasi, 2023)
This study aims to analyze the effect of Green Perceived Value (GPV) and Green Brand Knowledge on Purchase Intention to Buying Green Products through Attitude Towards Purchasing Green Products. The data was obtained directly through the distribution of questionnaires, Google Docs, and WhatsApp to consumers who have purchased Green Products. The number of respondents in this research was 200 people. Questionnaire results were processed using Smart PLS version 3.29. The results of hypothesis testing show: Functional Value affects Purchase Intention to Buying Green Products with Attitude Towards Purchasing Green Products as mediation. Conditional Value affects Purchase Intention to Buying Green Products with Attitude Towards Purchasing Green Products as mediation. Social Value that does not affect Purchase Intention to Buying Green Products with Attitude Towards Purchasing Green Products as mediation. Emotional Value affects Purchase Intention to Buying Green Products with Attitude Towards Purchasing Green Products as mediation. Green Brand Knowledge affects Purchase Intention to Buy Green Products with Attitude Toward To Purchase Green Products through Attitude Toward To Purchase Green Products.